Vermifiltration of Slaughterhousewaste Water: A Case Study for Kampala City Abattoir - Michelle .B. Ayebazamukama (Uganda Christian University, 2025)
This study showed the effectiveness of vermifiltration on slaughterhouse waste water at the Kampala city abattoir. Slaughterhouse waste water presented a significant environmental challenge due to its high organic load, nutrient content and presence of pathogens. Vermifiltration involves the use of earthworms specifically the type called Eisenia fetida and microorganisms as a biofilter in the degradation of the organic matter symbiotically. The major aim of the study was to investigate the effectiveness of the vermifilter in the treatment of this type of waste water. The treatment was executed into three buckets, one which was a control and the other two containing the earthworms whereby the effluent that was collected was assessed for various parameters that is BOD, COD, TSS, turbidity, TP, TN, FOG(fats. Oils and greases) and EC. This study also relied on calculating the peak flow rate and right hydraulic retention time for its effectiveness which was done for three days which was obtained as 6hours. The results were found to meet the permissible standards making it safe for discharge
Undergraduate